2020
DOI: 10.3390/ma13204505
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Analytical Study of Masonry Subjected to Uniaxial Cyclic Compression

Abstract: Structural evaluation of masonry against dynamic seismic actions invariably requires appropriate cyclic compression constitutive models. However, not many research studies have been dedicated to date to investigate the cyclic compression behaviour of masonry. Therefore, series of experimental investigation followed by analytical model verification were employed in this research to better understand the cyclic compression characteristics of masonry. Twelve masonry wallettes were experimentally tested under cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Experimental research on the behavior of masonry subjected to cyclic compression [48][49][50][51][52] has shown that the material behaves nonlinearly, with accumulation of nonreversible strains and stiffness degradation. The unloading and reloading branches follow different paths and the reloading stiffness decreases with every new cycle during the postpeak response.…”
Section: Unloading/reloading Behavior For Compressionmentioning
confidence: 99%
“…Experimental research on the behavior of masonry subjected to cyclic compression [48][49][50][51][52] has shown that the material behaves nonlinearly, with accumulation of nonreversible strains and stiffness degradation. The unloading and reloading branches follow different paths and the reloading stiffness decreases with every new cycle during the postpeak response.…”
Section: Unloading/reloading Behavior For Compressionmentioning
confidence: 99%
“…The investigations of destructions of monumental masonry vaults due to strong kinematic seismic loading have uncovered that the protection of these types of structures is a difficult technical task [1][2][3][4]. In particular, for historical structures located on seismic activity regions, the kinematic loading generated by seismic events are one of the most destructive factors [4,5]. Hence, monumental structures of this type, which are memorable heritage landmarks, have to be secured and, if necessary, strengthened against seismic loadings [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, monumental structures of this type, which are memorable heritage landmarks, have to be secured and, if necessary, strengthened against seismic loadings [6][7][8][9]. Taking into consideration the assessment methods which were proposed by different researchers [4][5][6][7][8][9], the numerical evaluation of damages in structures subjected to seismic events is significant stage in designing strengthening. Calculations with nonlinear plastic material models provide good quality data for strengthening the structural parts that are at risk of being destroyed by strong seismic events [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of compressed masonry structures has been presented in many domestic and foreign scientific publications [ 13 , 14 , 15 ]. There are also publications on the cyclic loading of masonry structures [ 16 , 17 , 18 ].…”
Section: Introduction To the Design Of Masonry Structuresmentioning
confidence: 99%